Palaeobiodiversity and Palaeoenvironments - Palaeobiodiversity and Palaeoenvironments (Springer Nature, 2026)
Palaeobiodiversity and Palaeoenvironments is a peer-reviewed international journal for the publication of high-quality multidisciplinary studies in the fields of palaeobiodiversity, palaeoenvironments and palaeobiogeography. Key criteria for the acceptance of manuscripts are a global scope or implications of problems on a global scale significant not only for a single discipline, a focus on the diversity of fossil organisms and the causes and processes of change in Earth’s history. The topics covered include: Systematic studies of all fossil animal / plant groups with a special focus on palaeoenvironmental investigations, palaeoecosystems and climate changes in Earth’s history, environment-organism interaction, comparison of modern and ancient sedimentary environments, palaeoecology and palaeobiogeography.
FI 0.67
Q3
Keywords: Earth; Space & Environmental Sciences; Paleontology; Paleobiology & Geobiology; Paleontología; Paleobiología; Geobiología; Acuerdos transformativos; Transformative agreements; Paleobiodiversidad; Paleoambientes; Paleobiogeografía